Cultural and Parental Standards as the Benchmark for Early Learning and Development Standards in Africa - Ejuu, Godfrey (International Journal of Current Research, 2012)
Recognition and inclusion of cultural parental expectations of their children at different stages of development is critical in formulating comprehensive early learning and development standards. While there has been significant research on ‘best practices’ from the west that are largely school based expectations of children at different stages in Uganda, there is a lack of research into traditional parental expectations of their children at different stages of development. This study explores cultural parental expectations of 160 parents of pre-schoolers that they wish to see inculcated into their children. Structured interview was used to collect data which was later analyzed descriptively. Result from this study may inform the process of developing a comprehensive early learning and development standard that is sensitive to both parental and school based standards so as to cater for a whole child.
Keywords: Early learning and development standards; Culture; Parental expectations; School competences